-8u+40=-5(u-5)

Simple and best practice solution for -8u+40=-5(u-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8u+40=-5(u-5) equation:



-8u+40=-5(u-5)
We move all terms to the left:
-8u+40-(-5(u-5))=0
We calculate terms in parentheses: -(-5(u-5)), so:
-5(u-5)
We multiply parentheses
-5u+25
Back to the equation:
-(-5u+25)
We get rid of parentheses
-8u+5u-25+40=0
We add all the numbers together, and all the variables
-3u+15=0
We move all terms containing u to the left, all other terms to the right
-3u=-15
u=-15/-3
u=+5

See similar equations:

| 1-r=-16+1-7r-2r | | -2-11=4x+14-3 | | 9/4x=11/4 | | 3(4y+1)=15 | | 5x-5x=6-3x | | -2(x+9)=-8x+18 | | 8x/3-5=19 | | 6x-7=9-2x | | 1-4b-b=7-4b | | 7(m+55)=63 | | 11(-2)+4y=-46 | | 5n-6=-10+4n | | 3(5-2x)=2(5x+1) | | 18n-(3n+4)=11 | | 5m+7-3=19 | | 20=-6x+7+1 | | 12x-8x+4x=9+10-3x-7=-6x-2+8x-9x-7+11+4 | | 7x+7=3(x-1) | | h8= 6 | | -5(x+1)=-7x+15 | | 19s-16s=-12 | | 9w-29=-7(w-5) | | 0.08x+8.3=6.14 | | 3.25=1/x-1.2 | | 8x+x-9x+x=17 | | b=7/6 | | 5(v-5)=-3-33 | | 6y-7-3y+3=0 | | 7a-3=3=3-2a | | 4^(3x-2)=5 | | 12s+s-13s+3s+3s=18 | | -40=13t |

Equations solver categories